Riedel's disease: Report of a case and review of the pathogenesis and therapeutics - Barreiro, Claudia; Fígoli, Luis; Praderi, Luis; Ormaechea, Ernesto; Paseyro, Ana; Rodríguez, Julio; Morelli, Raúl (Cirugía del Uruguay, 1997)
Riedel's disease is an infrequent pathology of unknown etiology and chronical course which affects the thyroid gland among other organs.